THE ROLE OF HBA1C IN CHRONIC KIDNEY DISEASE PROGRESSION IN TYPE 2 DIABETES MELLITUS PATIENTS: A LITERATURE REVIEW - Prasetya, Dini Amelia Rahmawati; Prasetya, Fajar Ahmad (HEARTY, 2026)
Type 2 diabetes mellitus (T2DM) is a leading cause of chronic kidney disease (CKD), contributing significantly to global morbidity, mortality, and healthcare burden. Glycemic control, primarily assessed by hemoglobin A1c (HbA1c), has traditionally been considered essential for preventing microvascular complications, including diabetic kidney disease (DKD). However, the relationship between HbA1c and CKD progression in patients with established CKD remains complex and controversial, particularly in advanced stages. This literature review, conducted according to PRISMA 2020 guidelines, systematically examined evidence from 10 selected studies (published 2013–2025) exploring the role of HbA1c in CKD progression among patients with T2DM. Studies included observational cohorts, longitudinal analyses, and one review, encompassing diverse populations and CKD stages. Key findings indicate that in early-to-moderate CKD (stages 1–3/4), higher mean HbA1c levels consistently predict faster eGFR decline and increased risk of progression, supporting the benefit of stricter glycemic control in these stages. In advanced CKD (stages 4–5), intensive glycemic control shows limited renal protective effects, with stronger associations observed for reducing cardiovascular events and mortality rather than slowing renal progression. HbA1c variability emerged as an independent predictor of adverse renal outcomes, including microalbuminuria development, non-linear eGFR trajectories, and rapid progression to end-stage kidney disease, potentially mediated by oxidative stress. Additionally, HbA1c reliability decreases in severe CKD due to altered red blood cell turnover and anemia, suggesting the need for alternative markers such as fructosamine. Patient factors, including African-Caribbean ethnicity, further modify these relationships. HbA1c plays a stage-dependent role in CKD progression in T2DM. Clinical management should prioritize individualized, stage-specific targets, emphasize glycemic stability, incorporate alternative monitoring tools in advanced disease, and account for patient-specific risk factors to optimize outcomes while minimizing hypoglycemia risk.